The Relationship Between Perceived Control and Hypothalamic–Pituitary–Adrenal Axis Reactivity to the Trier Social Stress Test in Healthy Young Adults - Liu, Qian; Wu, Jianhui; Zhang, Liang; Sun, Xiaofang; Guan, Qing; Yao, Zhuxi (Frontiers in Psychology, 2021)
Psychological factors can modulate the hypothalamic-pituitary–adrenocortical (HPA) axis activity toward stressors. Animal studies demonstrated that uncontrollability was one critical factor associated with HPA axis stress response, but the results in human studies were inconsistent. The current study adopted a standardized laboratory stress induction procedure, the Trier Social Stress Test (TSST), as the stressor to regulate the objective controllability level, and the participants were asked to rate their subjectively perceived control level toward the stressor and measured their cortisol stress responses (N = 54; 19 females, 35 males) to address this concern. Results showed that participants’ perceived control on the TSST was related to the cortisol stress response. In other words, under the stress of a certain objective controllability level, the lower the subjectively perceived control level, the greater the HPA axis response. This finding suggested that, in addition to objective controllability, subjectively perceived control is a psychological factor that regulates activation of the HPA axis.